2017
DOI: 10.3892/ijo.2017.4151
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of HOXA10 and HOXB4 in human medulloblastoma cell lines

Abstract: Medulloblastoma (MB) is a malignant childhood brain tumor which at molecular level is classified into at least four major subtypes: WNT, SHH, group C and group D differing in response to treatment. Previous studies have associated changes in expression levels and activation of certain HOX genes with MB development. In the present study, we investigate the role of HOX genes in two attributes acquired by tumor cells: migration and proliferation potential, as well as, in vivo tumorigenic potential. We analyzed UW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Previous studies indicated that HOXB4 plays a crucial role in cancer progression [24,32,[42][43][44][45]. EMT is important during tumor metastasis in which epithelial cells lose adhesion and acquire invasive ability [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that HOXB4 plays a crucial role in cancer progression [24,32,[42][43][44][45]. EMT is important during tumor metastasis in which epithelial cells lose adhesion and acquire invasive ability [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The HOXB family involvement in tumor EMT has yet to be fully investigated, and EMT-associated HOXBs in OV have rarely been reported [18][19][20][21][22]. Homeobox B4 (HOXB4) is an important transcription factor involved in the progression of lung, breast, prostate, and bladder cancer [23][24][25][26][27]. HOXB4 enhances proliferation and the stat3 pathway [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that HOXB4 plays an crucial role in cancer progression [24,32,[41][42][43][44]. EMT is important during tumor metastasis that epithelial cells to lose adhesion and acquire invasive ablibity [45][46][47][48].…”
Section: Hoxb4 Facilitates the Progression Of Ov In The Mouse Modelmentioning
confidence: 99%
“…The HOXB family involved in tumor EMT has yet to be fully investigated, and EMT HOXBs with OV have been rarely reported [18][19][20][21][22]. Homeobox B4 (HOXB4), an important transcription factor and involved in the progression of lung, breast, prostate, and bladder cancer [23][24][25][26][27]. HOXB4 enhances proliferation and stat3 pathway [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…progression of lung, breast, prostate, and bladder cancer [23][24][25][26][27]. HOXB4 enhances proliferation and the stat3 pathway [28][29][30][31][32].…”
mentioning
confidence: 99%